Digital Leadership Simplicity and Organizational Performance: the Roles of Work-From-Anywhere Effectiveness, Employee Engagement, and Attention Stability Among Indonesian Remote-Capable Workers - Nur Faliza; Masyhuri Husin; Ilzar Daud (CV. Sakura Digital Nusantara, 2026)
Purpose – This study investigates the effects of digital leadership on work-from-anywhere (FWA) effectiveness, employee engagement, and organizational performance among Generation Z employees in Indonesia. Methodology – A quantitative survey was distributed through LinkedIn to remote workers in Indonesian organizations. Structural Equation Modeling–Partial Least Squares (SEM-PLS) was used to examine relationships among digital leadership, FWA effectiveness, employee engagement, organizational performance, cross-platform work impedance, job-market interruption, and attention stability. Results – Digital leadership positively influenced FWA effectiveness, which subsequently improved employee engagement and organizational performance. Cross-platform work impedance negatively affected attention stability and FWA effectiveness, while job-market interruption reduced attention stability but had no direct effect on FWA effectiveness. Originality– Drawing on Job Demands-Resources theory, this study identifies digital leadership as an important organizational resource for reducing digital distractions in remote work. It provides theoretical and practical insights into managing Generation Z employees in FWA environments.